2003
DOI: 10.3346/jkms.2003.18.4.505
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomics Approach to Find Biomarkers in Gastric Cancer

Abstract: Gastric cancer is a very serious disease and is naturally resistant to many anticancer drugs. To reduce the mortality and improve the effectiveness of therapy, many studies have tried to find key biomarkers. Proteomic technologies are providing the tools needed to discover and identify disease-associating biomarkers. The proteomic study of gastric cancer establishes any specific events that lead to cancer, and it provides a direct way to define the true function of genes. Using two dimensional (2-D) electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
100
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 12 publications
7
100
0
1
Order By: Relevance
“…Transgelin 2, which has been reported to be overexpressed in gastric cancer (Ryu et al, 2003), was found to be upregulated in 11 of 16 HCC patients. This protein is thought to be involved in cell proliferation and migration, suggesting that its overexpression may be implicated in tumour progression.…”
Section: Discussionmentioning
confidence: 95%
“…Transgelin 2, which has been reported to be overexpressed in gastric cancer (Ryu et al, 2003), was found to be upregulated in 11 of 16 HCC patients. This protein is thought to be involved in cell proliferation and migration, suggesting that its overexpression may be implicated in tumour progression.…”
Section: Discussionmentioning
confidence: 95%
“…The over-expression of HSP27 in gastric cancer has been observed by several studies (8,25,26). In gastric cancer, over-expression of HSP27 may be associated with metastasis to the lymph nodes, advanced stage (III and IV) cancer, and shorter overall survival of patients (27,28), indicating that HSP27 has prognostic significance for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Transgelin, also known as SM22-α, of the calciumbinding protein family, is an actin-binding protein with a molecular weight of 22 kda. Transgelin was overexpressed in gastric cancer and renal cell carcinoma, and was capable of inducing igG responses in vivo in some patients (10)(11)(12). in order to identify a potential diagnostic marker for liver cancer and immunotherapy molecular targets, Shi et al (13) detected tumor antigens and tumor-associated antigens in patients with Hcc by serological analysis of cdna expression libraries (SereX).…”
Section: Discussionmentioning
confidence: 99%